DETERMINANTS OF WOMEN'S ENTREPRENEURIAL INTEREST: GENDER STEREOTYPICAL ROLES, SOCIAL SUPPORT, SELF-EFFICACY, AND ATTITUDES - Pinkan, Aurelia Reghina; Fatimah, Feti; Murtaliningtyas, Wenny (Universitas Muhammadiyah Tangerang, 2025)
The economic progress of a country in the field of entrepreneurship is no longer dominated by men, but also involves women as business actors. This study aims to analyze the influence of gender stereotypes, social support, self-efficacy, and personal attitudes on women's entrepreneurial interest in Jelbuk District, filling the gap in the literature on psychosocial factors in the context of gender entrepreneurship. The quantitative method was applied with purposive sampling techniques (sample of 150 respondents) and questionnaires as data collection instruments. Data analysis includes validity-reliability tests, classical assumptions, multiple linear regression, hypothesis tests (t-test and F-test), and determination coefficients. The results showed that the four variables had a partial significant effect (p < 0.05), with a simultaneous contribution of 75% (R² = 0.753). These findings strengthen social-cognitive theories and provide practical implications for governments and women's empowerment institutions in designing gender-based entrepreneurship programs. This research also confirms the need for inclusive policies to reduce stereotypical barriers and increase social support for female entrepreneurial aspirants.